Image 3_Association of SII and SIRI with incidence of cardiovascular disease in cardiovascular-kidney-metabolic syndrome: a prospective cohort study.tif - Chen Pengfei (22675154) (2025)
Background The relationship between systemic immune-inflammation biomarkers, the Systemic Immune-Inflammation Index (SII) and the Systemic Inflammation Response Index (SIRI), and cardiovascular disease (CVD) in cardiovascular-kidney-metabolic (CKM) syndrome remains unclear. Methods Individuals with CKM syndrome at stages 0–3 from UK Biobank were included in this study. Cox regression models were used to assess the association of SII and SIRI with incidence of CVD. Restricted cubic spline (RCS) models were applied to examine nonlinear longitudinal associations. Subgroup stratified by CKM stages were analyzed. Results A total of 301,631 participants with CKM stages 0 (14.1%), 1 (19.4%), 2 (56.7%), and 3 (9.8%) were included in this study. During a median follow-up of 13.0 years, CVD incidence occurred in 35,782 (11.86%) participants. After adjustment, the elevated SII (HR: 1.07, 95% CI: 1.05–1.10, p < 0.001) and SIRI (HR: 1.31, 95% CI: 1.26–1.37, p < 0.001) were associated with the risk of CVD incidence. RCS analyses indicated a U-shaped association for SII and a monotonic increase for SIRI. Subgroup analyses revealed significantly stronger associations between both SII and SIRI and the incidence of CVD with CKM stages. Conclusion As the main systemic immune-inflammation biomarkers, the elevated SII and SIRI in CKM syndrome were significantly associated with increased risk of CVD incidence.